Cross-cultural adaptation, reliability and validity of the persian version of the functional assessment scale for acute hamstring injuries - Mohammad Hadadi; Farzaneh Haghighat (Journal of Orthopaedic Surgery and Research)
Abstract Background The Functional Assessment Scale for Acute Hamstring Injuries (FASH) which measure symptom’s severity and impact on physical activity and sports ability in individuals with acute hamstring muscle injury, is not available in Persian. The aim of this study was to translate and cross-culturally adapt the FASH questionnaire to Persian and to assess the psychometric properties of the translated version. Methods The Persian-translation and cross-cultural adaptation processes were based on World Health Organization method. A total of 160 participants compromising of four groups: (1) acute hamstring injury (N = 40), (2) other lower extremity injury (N = 40), (3) risk of acute injury (N = 40), and (4) healthy control (N = 40) were recruited to complete the Persian version of FASH (FASH-P) questionnaire twice with an interval of 48–60 h. The Short Form Health Survey (SF-36) and Lower Extremity Functional Scale (LEFS) were used to assess the criterion validity. Test-retest reliability, internal consistency, criterion validity, Dimensionality and floor/ceiling effects were evaluated to assess the FASH-P psychometric properties. Results The FASH questionnaire were translated to Persian without any major problems. The FASH-P showed excellent power of differentiation because the scores were significantly different among the four groups. Regarding psychometric performances, excellent test–retest reliability (Intraclass correlation coefficient of 0.997) and a high level of internal consistency (Cronbach’s alpha of 0.966) were observed. The FASH-P total score was significantly correlated with SF-36 and LEFS questionnaires representing an excellent criterion validity. No floor or ceiling effect were found for total score in Hamstring muscle injury group. Conclusions Due to the excellent psychometric performance, the FASH-P can be used as a reliable and valid tool for evaluating the severity of symptoms and sports ability in Persian-speaking patients with hamstring muscle injury.